Soybean Sudden Death Syndrome Influenced by Macronutrient Fertility on Irrigated Soybean in a Corn/Soybean Rotation - E. A. Adee; D. Ruiz Diaz (Kansas Agricultural Experiment Station Research Reports, 2015)
The effects of nitrogen (N), phosphorus (P), and potassium (K) fertilization on a corn/ soybean cropping sequence were evaluated from 1983 to 2014, with corn planted in odd years. We observed a relationship between the P rate applied during the corn years and the severity of sudden death syndrome (SDS) in 2014 soybean.
Keywords: soybean sudden death syndrome; soybean sudden death syndrome severity; irrigated soybean; macronutrient fertility; soybean yield; Kansas River Valley Experiment Field